Corrigendum to "Developing picture storybooks assisted by word search puzzle to improve elementary students' indonesian vocabulary mastery" - Andhini Pramudita; Nugraheti Sismulyasih SB (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This corrigendum addresses two errors in the originally published version of this article. First, the name of the second author in the cited work was inadvertently reversed in the citation metadata. The in-text citation was published as "Kurniawati & Santy, 2022" on pages 448 and 452, whereas it should read "Kurniawati & Yulianti, 2022". Correspondingly, the reference-list entry on page 463 was published as "Kurniawati, W., & Santy, Y. (2022)" and should read "Kurniawati, W., & Yulianti, S. (2022)", reflecting the correct author name, Santy Yulianti. Second, in Table 3, "Results of media expert assessment of picture storybooks," on page 454, the percentage for the "Language and readability" aspect was incorrectly printed as "8.,5%"; the correct value is "87,5%". These corrections do not affect the results, interpretation, or conclusions of the article. The authors sincerely apologize for these errors and any inconvenience they may have caused. The online version of the article has been amended accordingly.